A new approach for determination of interlaminar normal/shear stresses in micro and nano laminated composite beams. Issue 10 (July 2019) - Ghasemi, Ahmad Reza; Mohandes, Masood
In this article, a displacement model for micro and nano laminated composite Timoshenko beam is presented. The layer-wise displacement model is refined in order to calculate interlaminar stresses correctly. In the presented model, the behavior of displacements at the interface of adjacent layers is modeled by transverse and tangential springs of high stiffnesses. The reaction of various springs in different directions indicates an approximation of transverse and tangential interactions between adjacent layers of the laminated beam. Using the presented model and also modified couple stress theory, the in-plane stresses of the laminated composite Timoshenko beam subjected to different boundary conditions including simply–simply supported, clamped–clamped, and clamped–free are studied. In addition, the effects of material length scale parameter and elastic foundation on the stresses are investigated. The advantage of this method is accurate calculation of interlaminar stresses without using the equilibrium equations.